KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) DAN NHT (NUMBERED HEADS TOGETHER) DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KECERDASAN MAJEMUK SISWA PADA POKOK BAHASAN FUNGSI KELAS VIII SMP NEGERI SE-KABUPATEN NGAWI TAHUN PELAJARAN 2014/2015 - Astuti, Indra Puji; Budiyono, Budiyono; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to determine the effect of learning model, multiple intelligences (logical-mathematical, linguistic, and interpersonal), and their interaction toward mathematics learning achievement. The learning models compared were the cooperative learning of Teams Assisted Individualization with scientific approach (TAI-PS), Numbered Heads Together with scientific approach (NHT-PS), and classical learning with scientific approach (classical-PS). This research was a quasi-experimental research with 3x3 factorial design. The population of this research was all students in Grade VIII of Junior High School of Ngawi Regency in academic year 2014/2015. This research used stratified cluster random sampling technique. The data analysis techniques of this research used two-way analysis of variance with unequal cells. With the 5% level of significance the result were as follows. (1) TAI-PS gave better mathematics learning achievement than NHT-PS and classical-PS. In addition, NHT-PS gave the same mathematics learning achievement as classical-PS. (2) Students with logical-mathematical and interpersonal intelligence had better mathematics learning achievement than students with linguistic intelligence. Students with logical-mathematical intelligence had the same mathematics learning achievement as students with interpersonal intelligence. (3) At the TAI-PS, students with logical-mathematical, linguistic, and interpersonal intelligence got same mathematics learning achievement. At the NHT-PS, students with logical-mathematical, linguistic, and interpersonal intelligence got same mathematics learning achievement. At the classical-PS, students with logical-mathematical and interpersonal intelligence had better mathematics learning achievement than linguistic intelligence. In addition, students with logical-mathematical intelligence had the same mathematics learning achievement as students with interpersonal intelligence. (4) At the logical-mathematical intelligence, TAI-PS, NHT-PS, and classical-PS gave the same mathematics learning achievement. At the linguistic intelligence, TAI-PS gave the same mathematics learning achievement as NHT-PS. In addition, NHT-PS and TAI-PS gave better mathematics learning achievement than classical-PS. At the interpersonal intelligence, TAI-PS, NHT-PS, and classical-PS gave the same mathematics learning achievement.Keywords: Multiple Intelligences, Classical, NHT (Numbered Heads Together), Scientific Approach, TAI (Team Assisted Individualization)